Some Developmental Distinction Among Obese and Extremely Thin Children - Chrzanowska, Maria (Anthropological Review, 1993)
Some developmental distinction among obese and extremely thin children, were studied in a population of 6,540 individuals. Certain ontogenetic characteristics of obese as opposed to extremely thin children were observed.